Analysis of Financial Statements to Assess Financial Performance of Food and Beverage Industry Companies on the Indonesia Stock Exchange - Sulistyowati, Ari (Advances In Social Humanities Research, 2024)
Financial performance assessments are based on increased sales. This can be reflected in a report, a report that describes the development of the company's financial performance in a certain period. These reports are commonly called financial statements. In order for financial statements to be meaningful to interested parties, it is necessary to conduct a relationship analysis of the posts in the financial statements, which is often called financial statement analysis. The purpose of this study is to find out how the financial performance of PT. Sentra Food Indonesia Tbk, PT Mayora Indah Tbk, and PT Indofood Sukses Makmur Tbk based on an analysis of liquidity, solvency, and profitability ratios. The data analysis method used is a quantitative descriptive method using the measurement of liquidity, solvency, and profitability ratios. The results of the study show that financial performance in terms of liquidity as measured by the Current Ratio during the pandemic there was a decline in performance at PT. Sentra Food Indonesia, while in terms of solvency and profitability, the value of debt to equity ratio and return on equity of the three companies tends to fluctuate from year to year.